2003
DOI: 10.1200/jco.2003.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled Trial of Combined Pentoxifylline and Tocopherol for Regression of Superficial Radiation-Induced Fibrosis

Abstract: Six months' treatment of combined PTX/Vit E can significantly reduce superficial RIF. Synergism between PTX and Vit E is likely, as treatment with each drug alone is ineffective, but these results require confirmation in larger series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
199
0
21

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(221 citation statements)
references
References 24 publications
1
199
0
21
Order By: Relevance
“…Second, preliminary results have shown that TGF-b antagonists may inhibit or reduce the action of this growth factor (Border et al, 1990;Shah et al, 1992;Delanian et al, 1999;Lefaix et al, 1999;Delanian et al, 2003). The significant reduction of chronic RT damage obtained with the pentoxifylline and alpha-tocopherol combination (Delanian et al, 2003) does not support the concept that established RT sequelae such as radiation-induced subcutaneous fibrosis are irreversible. Third, evidence from the first analysis of the ATAC (Arimidex, Tamoxifen Alone or in Combination Trialists Group) trial supports the use of aromatase inhibitors such as anastrozole for the adjuvant treatment of early breast cancer in postmenopausal women (Baum et al, 2002).…”
Section: Discussionmentioning
confidence: 59%
“…Second, preliminary results have shown that TGF-b antagonists may inhibit or reduce the action of this growth factor (Border et al, 1990;Shah et al, 1992;Delanian et al, 1999;Lefaix et al, 1999;Delanian et al, 2003). The significant reduction of chronic RT damage obtained with the pentoxifylline and alpha-tocopherol combination (Delanian et al, 2003) does not support the concept that established RT sequelae such as radiation-induced subcutaneous fibrosis are irreversible. Third, evidence from the first analysis of the ATAC (Arimidex, Tamoxifen Alone or in Combination Trialists Group) trial supports the use of aromatase inhibitors such as anastrozole for the adjuvant treatment of early breast cancer in postmenopausal women (Baum et al, 2002).…”
Section: Discussionmentioning
confidence: 59%
“…102 Combining agents with differing therapeutic targets (such as pentoxifylline (PTX), which improve perfusion due to vasodilatation and is anti-inflammatory, and Vitamin E, an antioxidant) may be beneficial. [103][104][105][106] These medications have been recommended by some authors, despite the lack of large randomised-controlled trials (RCTs). 107 …”
Section: Abdominal Visceral Painmentioning
confidence: 99%
“…α-Tocopherol is the major antioxidant in the serum [55]. Perturbations of the oxidant-antioxidant equilibrium including α-tocopherol were shown to be associated with the toxicity of radiotherapy [56,57] or chemotherapy [58]. In prior reports, a decrease of serum α-tocopherol concentrations has been noted during the administration of systemic chemotherapy [52,53,59,60].…”
Section: Discussionmentioning
confidence: 99%